Implementasi Konsep Pawongan Dalam Membangun Kerukunan Umat Beragama Di Kabupaten Buleleng - Yanti, Komang Heri (Widya Sandhi, 2024)
Every individual or society is obliged to build a harmonious life with each other. No one can walk alone without involving other people, especially those related to common interests such as death, marriage, customs or other interests. The principle of maintaining harmony is of course highly emphasized. Likewise in relation to relations between religious believers, relations with the environment, groups, and so on. It is not uncommon for relations between groups to be disturbed by internal factors such as a lack of openness and external factors such as incitement or inaccurate information obtained. To deal with problems like this, adaptation strategies by implementing the values ​​of harmony contained in the Pawongan concept are emphasized. Pawongan as a noble heritage contains a message of harmony that must be implemented by every individual in society.